IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING FREE POETRY THROUGH THE REAL EXPERIENCE METHOD IN CLASS IV STUDENTS OF MADRASAH IBTIDAIYAH NEGERI 1 WEST ACEH ACADEMIC YEAR 2022/2023 - Risnawati, Cut; Lidan, M (Program Studi Pendidikan Bahasa Indonesia FKIP-UNIVA Medan, 2022)
This study aimed to determine